2023
DOI: 10.1186/s12891-022-06096-w
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of osteoporosis using radiomics analysis derived from single source dual energy CT

Abstract: Background With the aging population of society, the incidence rate of osteoporosis is increasing year by year. Early diagnosis of osteoporosis plays a significant role in the progress of disease prevention. As newly developed technology, computed tomography (CT) radiomics could discover radiomic features difficult to recognize visually, providing convenient, comprehensive and accurate osteoporosis diagnosis. This study aimed to develop and validate a clinical-radiomics model based on the monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Clinical data and demographic traits [160,161] have been employed to identify individuals with osteoporosis or osteoporotic fractures, playing a pivotal role in the development of various tools for osteoporosis assessment [162]. The inclusion of clinical characteristics (such as age, sex, and risk factors as per the National Osteoporosis Foundation Guidelines [145]) in BMD assessment using DEXA has previously shown promising results in predicting osteoporosis, as demonstrated by Wang et al [104]. Their radiomics clinical model achieved an AUC of 0.988, compared with an AUC of 0.902 with radiomics alone (although this difference was not statistically significant, p = 0.643).…”
Section: Advantages and Efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical data and demographic traits [160,161] have been employed to identify individuals with osteoporosis or osteoporotic fractures, playing a pivotal role in the development of various tools for osteoporosis assessment [162]. The inclusion of clinical characteristics (such as age, sex, and risk factors as per the National Osteoporosis Foundation Guidelines [145]) in BMD assessment using DEXA has previously shown promising results in predicting osteoporosis, as demonstrated by Wang et al [104]. Their radiomics clinical model achieved an AUC of 0.988, compared with an AUC of 0.902 with radiomics alone (although this difference was not statistically significant, p = 0.643).…”
Section: Advantages and Efficacymentioning
confidence: 99%
“…These features capture intricate details in the images (beyond the human eye), enabling a more comprehensive understanding of the underlying tissue characteristics. Radiomics and texture analysis with deep learning techniques have also been used to analyze trabecular bone structure in CT images, providing insights into bone quality and microstructure that are not attainable through DEXA or visual measurements alone, thereby improving the accuracy of diagnosing osteoporosis [104,105]. While many studies have focused on the use of AI for classifying or detecting osteoporosis, they often suffer from limitations, such as single-center designs, limited patient samples, and a lack of validation in real clinical settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative computed tomography (QCT) is an accurate measurement offering a sophisticated and precise method for BMD assessment, with cross-sectional imaging providing a detailed volumetric analysis ( 13 ). This technology is superior to dual-energy X-ray absorptiometry (DXA) in differentiating between trabecular and cortical bone, offering a three-dimensional perspective that is less likely to be confounded by extraneous factors such as spinal degeneration or aortic calcifications ( 14 ). A previous study conducted by Almomen et al demonstrated that in women diagnosed with AIS, those with more pronounced spinal curvature, as indicated by higher Cobb angle measurements, are more likely to have lower BMD values, as determined through DXA assessments ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical value of DECT-derived radio(geno)mics features has been reported for diagnosis of malignancy, depicting genetic, molecular, and histological features in different tumor types; evaluating tumor invasiveness; predicting tumor staging; characterization of malignant lymph nodes, predicting patient outcome and survival, and predicting and evaluating tumor response in different tumor types [81][82][83][84][85][86][87] [Figure 23]. There are also preliminary data that support the possible value of DECT-derived features as imaging biomarkers in other non-oncologic applications such as the diagnosis of pulmonary embolism, type 2 diabetes mellitus, osteoporosis, liver fibrosis, and carotid stenosis, the assessment of lung interstitial disease or Crohn´s disease activity, or acute pancreatitis, the characterization of adrenal masses, and the location and analysis of kidney stones [88][89][90][91][92][93][94][95][96] [Figure 24]. The robustness of features has been identified as pivotal for the clinical implementation.…”
mentioning
confidence: 97%